HUBUNGAN KEKUATAN OTOT TUNGKAI DENGAN AKURASI SHOOTING PADA ATLET FUTSAL - Faiz Faozi; Mochammad Latif; Dede Taufik Hidayatulloh; Ade Wahyud (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2024)
This study aims to determine whether or not there is a relationship between leg muscle strength and shooting accuracy in female futsal athletes at the Cidahu Academy Futsal Zone (ZFCA). This research design uses quantitative methods. This research is correlational in nature, namely explaining the relationship between variables by analyzing numerical data (numbers) using statistical methods through hypothesis testing. The population in this study were female futsal athletes from the Cidahu Academy Futsal Zone (ZFCA), totaling 20 athletes. This research used a total sampling technique, so the samples used for this research were all female futsal athletes from the Cidahu Academy Futsal Zone (ZFCA), totaling 20 athletes. The instruments used in this research were the leg dynamometer test for leg muscle strength and the targeted goal shooting test for shooting accuracy. Data analysis uses a correlation test with a significance level of 5%. The research results show that: (1) There is a significant relationship between leg muscle strength and futsal shooting accuracy with a correlation coefficient of 0.947, greater than the rejection limit of 5% = 0.444. with the results of the F test showing Fcount = 157.230 which is greater than Ftable with a significance level of 5% = 4.41